Respuesta :
(4-3√3)(2-√3)
(4 - 3√3)(2 - √3) -> 4 x 2 = 8
(4 - 3√3)(2 - √3) -> -3√3 x 2 = -6√3
(4 - 3√3)(2 - √3) -> 4 x -√3 = -4√3
(4 - 3√3)(2 - √3) -> -3√3 x -√3 = 3√3 x √3 = √9√3 x √3 = √27 x √3 = √81 = 9
∴ (4-3√3)(2-√3) = 8 - 6√3 - 4√3 + 9
8 - 6√3 - 4√3 + 9
= 17 - 6√3 - 4√3
= 17 + (- 6 - 4)√3
= 17 - 10√3
Without decimals, you cannot go any further.
Tell me if I was confusing at all :)
UPDATED... AGAIN...
(4 - 3√3)(2 - √3) -> 4 x 2 = 8
(4 - 3√3)(2 - √3) -> -3√3 x 2 = -6√3
(4 - 3√3)(2 - √3) -> 4 x -√3 = -4√3
(4 - 3√3)(2 - √3) -> -3√3 x -√3 = 3√3 x √3 = √9√3 x √3 = √27 x √3 = √81 = 9
∴ (4-3√3)(2-√3) = 8 - 6√3 - 4√3 + 9
8 - 6√3 - 4√3 + 9
= 17 - 6√3 - 4√3
= 17 + (- 6 - 4)√3
= 17 - 10√3
Without decimals, you cannot go any further.
Tell me if I was confusing at all :)
UPDATED... AGAIN...
You have two binomials. I would just FOIL them:
First: 4 x 2 = 8
Outside: 4 (-√3) = -4√3
Inside: -3√3 (2) = -6√3
Last: -3√3 (-√3) = 9
Addummup: 8 - 4√3 - -6√3 + 9 = 17 - 10√3